The impact of parental migration background on cardiometabolic health in European children. (20th October 2021) - Lindblad, A; Ahrens, W; Winkler, V; Lissner, L; Mehlig, K
Abstract: Background: There is accumulating evidence that children from migrant families have higher risk of developing overweight and obesity than their peers in the host population. This study aims to investigate the association between parental migration and cardiometabolic health, including the metabolic score and its components, in children and adolescents in Europe. Methods: Data was collected from 8, 828 children (aged 2-17) in eight European countries included in the multicentre IDEFICS/I.Family cohort. Multilevel linear regression models were used (accounting for correlations between siblings) to investigate the association between parental migration background (one or two migrant parent(s) vs native parents) and the cardiometabolic health outcomes body mass index (BMI), metabolic score and its individual components. Outcome variables were parametrized as age and sex-specific z-scores. We controlled for socioeconomic indicators, maternal weight status, as well as lifestyle and dietary patterns. Results: We found a higher mean BMI z-score (+0.24 SD, p < 0.001) and overall metabolic z-score (+0.28 SD, p < 0.001) among children with two migrant parents in comparison to children with two native parents. No differences could be seen between children with one versus no migrant parent. The effects were attenuated when controlling for maternal weight status and levels of sport club activity. Parental education modified the associations for some health outcomes (BMI and waist circumference) such that they were more pronounced in children with low parental education. Conclusions: European children and adolescents with two-parent migration background seem to be at higher risk of developing adverse cardiometabolic health than their peers. Children with one migrant parent seem to have similar risk as children with native parents. Maternal BMI and levels of physical activity partly explained the higher risk, a risk which was more prevalent in families with lower education level. Key messages: European children and adolescents with two-parent migration background have higher risks of developing adverse cardiometabolic health than their peers with one or two native parents. The higher risk of being overweight and having cardiometabolic risk factors among children with two-parent migration background was most pronounced in families with low level of education.